Clinical cases of Hepatitis E in children - O. S. Pozdeeva; O. G. Mokhova; M. N. Kankasova (LLC "Diagnostics and Vaccines", 2020)
The article presents an analysis of the literature data on the prevalence of viral hepatitis E, the peculiarities of the course of the disease, including in children, and describes own cases of viral hepatitis E in children.Viral hepatitis E is a common infection worldwide. Sporadic and group cases of the disease are also registered on the territory of the Russian Federation. Epidemio-logical and clinical features of the course of the disease depending on the genotype were revealed. Children rarely get sick with manifest forms all over the world.Infection of the fetus and newborns with the development of fulminant hepatitis is typical for developing countries. The development of chronic infection is described in children who have undergone liver transplantation. In the Udmurt Republic, during the period of rising incidence of viral hepatitis A, 4 cases of viral hepatitis E were registered in 2017 in different age groups and different clinical manifestations. Registered cases of viral hepatitis E in children in the Russian Federation determine the need for mandatory examination of patients with cytolysis syndrome for this infection.